Combating Human Trafficking in Nigeria: An Evaluation of State Policies and Programmes - Duru, Emmanuel Joseph Chukwuma; Ogbonnaya, Ufiem Maurice (Richtmann Publishing, 2012)
This paper examines the social problem of trafficking in human beings in Nigeria. It considers the root causes of the problem,the socio-economic implication of human trafficking, its recent global dimension and the policies and programmes of the Nigerian state incombating this ugly phenomenon. The paper made predominant use of secondary sources of data. Findings reveal that though the statehas certain policies and programs aimed at combating human trafficking, the problem persists because the institutions saddled withthese responsibilities are fundamentally weak. The paper, therefore, recommends certain measures to help in tackling the problem ofhuman trafficking in Nigeria.